Generic Animation Method for Multi-Objects in IFS Fractal Form - Tedjo Darmanto; Iping Supriana; Rinaldi Munir (Journal of ICT Research and Applications, 2016)
Both non-metamorphic animation and metamorphic animation of objects or multi-objects in IFS fractal form as basic animation method can be implemented by a modified version of the random iteration algorithm as basic algorithm. In this way it is possible to create an attractive animation based on the combination of both animation methods as a generic animation method, as discussed in this paper. The proposed method can be used as an alternative for or as an extension of the existing animation methods in classical geometry, which are restricted to objects with regular forms. The proposed method can be used to produce more attractive media for interactively learning about the behavior of manipulated objects of any form.